High thermoelectric performance of half-Heusler ZrXPb (X = Ni, Pd, and Pt) compounds from first principle calculation. (1st September 2021) - Jiang, Quanwei; Wan, Rundong; Zhang, Zhengfu; Lei, Ying; Tian, Guocai
Abstract: Half-Heusler compounds have distinguished themselves as outstanding thermoelectric materials on account of high temperature stability and large thermopower. However, the dimensionless figure of merit of traditional half-Heusler alloys remains low. In this study, we investigate the thermoelectric performance of novel Zr X Pb ( X = Ni, Pd, and Pt) ternary compounds by semi-classical Boltzmann transport theory combining with deformation potential. The n-type ZrNiPb and ZrPtPb exhibits obviously large ZT values of 1.71 around 650 K and 1.75 around 1200 K, with 1.17 × 10 20  cm −3 and 3.43 × 10 20  cm −3, respectively. The electron and phonon structure calculations demonstrate that for the n-type Zr X Pb ( X = Ni, Pd, and Pt) compounds, doping at Pb site can not only modify the carrier concentrations but also significantly decrease the lattice thermal conductivity. These investigations are expected to be beneficial to the exploration of novel high ZT thermoelectric materials.